ANALISIS KERAGAMAN HAYATI TANAMAN PADI (Oryza sativa, L) - Hanifah Mariah Azhar dan Darwati Susilastuti (Fakultas Pertanian Universitas Borobudur, 2019)
Analysis of the diversity of paddy is descriptive quantitatively and qualita-tively. The ecosystem diversity of paddy in Indonesia is present in both terrestrial and water ecosystems. Based on the cultivation system, paddy is distinguished over wetland paddy, upland paddy and swampy paddy. In the water ecosystem there are types of wetland paddy and swampy paddy whereas in terrestrial eco-systems there are types of upland paddy and wild paddy. Species diversity of paddy, there are two varieties of cultivated paddy species namely Oryza sativa and O. glaberrima, Cultivated of paddy in Indonesia is O. sativa . The wide genetic diversity is reflected by the large number of current pad-dy varieties. During this time, the characterization of genetic material is generally done on the basis of morphological markers, which require intensive observation and it is very difficult to distinguish individuals with close kinship relations be-cause of the influence of environmental factors. Keywords: ecosystem diversity, species diversity, genetic diversity, paddy.